The Use of Very High-Doses of Baclofen for the Treatment of Alcohol-Dependence: A Case Series - de Beaurepaire, Renaud (Frontiers in Psychiatry, 2014)
Baclofen, particularly high-dose baclofen, has recently emerged as a treatment of major interest for alcohol-dependence. However, baclofen has many potentially dangerous side effects, and the maximal dose of baclofen that may be used is a matter of discussion. Here, the author analyses the medical charts of the last 100 patients seen in his clinic, 17 of whom have been taking a very high dose of baclofen, that is to say, more than 300mg per day. The analysis of the charts shows that the very high doses baclofen were justified in almost all the cases. Side effects are analyzed.